Plant macrofossil, peat geochemical and chronological data from sub-Arctic European peatlands - Piilo, Sanna; Väliranta, Minna (Zenodo, 2022)
This dataset consists of raw data from peat records analysed for plant macrofossils, peat geochemical properties supplemented by chronological control data from high-latitude Sweden, Finland and European Russia. Altogether, 33 peat cores were analysed from 16 peatlands. Peat cores were collected from seasonally thawed active peat layer with a box corer or a so-called Russian corer. Peat records cover both currently intermediate (n= 25) and dry (n= 8) surfaces. Majority of the sites (n= 12) are permafrost peatlands either with sporadic or discontinuous permafrost. Changes in peatland vegetation and peat and carbon accumulation were studied to resolve how high-latitude peatlands react to past and recent changes in climate. Peat properties were examined for bulk density, carbon (C), nitrogen (N) and C/N ratio. C accumulation was calculated for the past two millennia. To establish chronological control, peat layers were dated with 210Pb and radiocarbon 14. To create age-depth models we used Plum and the ages retrieved form the models are found in this dataset. The data have been analysed between 2016 and 2020. More information about the methods can be found from Piilo et al. “Consistent centennial-scale change in European sub-Arctic peatland vegetation towards Sphagnum dominance – implications for carbon sink capacity”. Global Change Biology.